Love in a changing Greek climate, and other essays - Just, Roger (Cambridge Scholars Publishing, 2018)
This book comprises eight essays concerned with the ethnography of Greece, and in particular of the village of Spartokhori on the small Ionian island of Meganisi, Lefkadha, where, between 1977 and 1980, the author conducted anthropological fieldwork. For the most part, the essays focus on aspects of family, kinship and gender as they were to be found in what was, in the 1970s, a remote, rural community. Greek society has, of course, undergone profound changes over the last forty years, and these essays thus serve to document a way of life that has now virtually disappeared. Importantly, however, they also deal with the transformation of rural Greek society as it was occurring at the time. The book will appeal to social anthropologists, sociologists and historians of Modern Greece, and to anyone interested in rural Mediterranean society--back cover.